MAGE-A Antigens and Cancer Immunotherapy - Zajac, Paul; Schultz-Thater, Elke; Tornillo, Luigi; Sadowski, Charlotte; Trella, Emanuele; Mengus, Chantal; Iezzi, Giandomenica; Spagnoli, Giulio C. (Frontiers in Medicine, 2017)
MAGE-A antigens are expressed in a variety of cancers of diverse histological origin and germinal cells. Due to their relatively high tumor specificity, they represent attractive targets for active specific and adoptive cancer immunotherapies. Here we (i) review past and ongoing clinical studies targeting these antigens, (ii) analyze advantages and disadvantages of different therapeutic approaches and (iii) discuss possible improvements in MAGE-A-specific immunotherapy approaches.